Acción Hemoaglutinante, Anticoagulante y Antimicrobiana Obtenidas de los Tubérculos Andinos - Aguas Salazar, Antonny David (2019)
The main objective of this research was to determine the hemagglutinating, anticoagulant and antimicrobial action of the aqueous extracts of the Andean tubers Tropaeolum tuberosum (Mashua) and Oxalis tuberosa (Oca) acquired in the popular markets of the city of Riobamba, of each species an aqueous extract was prepared in physiological saline solution by mechanical disruption using mortar and piston, the crushed was filtered on fine nylon mesh and centrifuged to obtain a clear supernatant. The biological activity was determined by evaluating in the aqueous extracts of the tubers, the haemagglutinating action on a suspension of human erythrocytes at 5% of groups A, B and O, the anticoagulant or procoagulant action on human plasma poor in platelets by measuring the TP and aPTT and bacteriostatic or bactericidal antimicrobial action through the disc diffusion method on American Type Culture Collection (ATCC) bacteria of the species Staphylococcus aureus, Escherichia coli, Enterococcus fecalis. The results of the haemagglutination experiments showed the presence of lectins able to agglutinate nonspecifically the red blood cells of blood groups A, B and O, likewise, the lengthening of the TP and the shortening of the aPTT determined the anticoagulant and procoagulant action respectively of the aqueous extracts of both tubers on the plasma proteins of the coagulation, in addition, the inhibition of the bacterial growth of the ATCC strain of E. coli with a halo of 12 mm, demonstrated the antimicrobial action of the aqueous extract of O. tuberosa, being this the only bacterial species inhibited and the only evaluated aqueous extract that exhibits this activity.